Pengaruh Perputaran Modal Kerja, Perputaran Kas, Dan Perputaran Persediaan Terhadap Profitabilitas (Studi Kasus PT. Bidang Perkebunan Kelapa Sawit Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Adnin Nur Aini Agustin; Siti Ma’sumah; Riztina Dwi Setyasih; Sania Ferika; Muftikhatur Rohmah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the influence of working capital turnover, cash turnover, and inventory turnover on profitability in oil palm plantation companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Profitability is measured using Return on Investment (ROI) as the primary indicator for assessing a company's financial performance. A quantitative approach was used, with secondary data collected using data documentation and purposive sampling. Data analysis was performed using statistical tests using SPSS version 24 software. The results indicate that partially, working capital turnover, cash turnover, and inventory turnover do not have a significant effect on profitability. However, simultaneously, all three variables significantly influence company profitability. This finding implies that integrated management of working capital elements can impact the financial performance of companies in the oil palm plantation sector.